Iron-molybdenum / NC catalyst and preparation method and application thereof
By using an iron-molybdenum/NC catalyst in a zinc-air battery, the catalyst solves the problem of slow kinetics of the cathode material of zinc-air battery by forming Fe3C and Mo2C heterojunction structures on a regular dodecahedral substrate and wrapping carbon nanotubes, achieving efficient oxygen reduction reaction and long-term stability.
Patent Information
- Application Number
- CN202411818385.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The cathode materials of existing zinc-air batteries are slow in the oxygen reduction reaction, resulting in low battery reaction efficiency, and the commonly used platinum-based catalysts are costly and have poor stability, limiting their commercial value.
Iron-molybdenum/NC catalyst was used, which was prepared by forming Fe3C and Mo2C heterojunction structures on a dodecahedral substrate and wrapped by carbon nanotubes, combined with a constant temperature oil bath self-assembly strategy and a nitrogen/hydrogen mixed calcination reduction method.
Excellent oxygen reduction reaction activity and long-term stability were achieved. The starting potential of ORR reached 0.972V under 0.1M KOH medium, the half-wave potential was 0.901V, and the potential attenuation was only 14mV after 10,000 cycles of CV, which had a charge and discharge stability of 380h.
Smart Images

Figure CN119650718A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an iron-molybdenum / NC catalyst and a preparation method and application thereof, belonging to the technical field of electrocatalysts and preparation thereof. Background Art
[0002] Rechargeable liquid zinc-air batteries (ZABs) are one of the most promising energy conversion devices, with broad commercial prospects such as high power density, environmental friendliness, high safety and low cost.
[0003] However, the oxygen reduction reaction (ORR) in the discharge process of ZABs plays a dominant role in the entire battery reaction due to its slow kinetics. Platinum (Pt)-based catalysts are widely used in ORR due to their high catalytic activity and high selectivity, but their high cost and poor stability limit their commercial value. Therefore, based on the above problems, it is very important to explore non-precious metal catalysts with high ORR activity and stability to reduce costs and industrial production. Summary of the invention
[0004] The present invention aims at the above technical problems existing in cathode materials of existing zinc-air batteries and provides an iron-molybdenum / NC catalyst for long-term charge and discharge cycle stability of zinc-air batteries and a preparation method thereof.
[0005] The technical solution of the present invention:
[0006] One of the objects of the present invention is to provide a method for preparing an iron-molybdenum / NC catalyst, which comprises the following steps:
[0007] (1) dissolving the metal salt, the organic ligand and the surfactant in DMF respectively, stirring them by ultrasonic until they are completely dissolved and then mixing them evenly, placing them in an oil bath and stirring at a constant temperature to obtain a reaction solution;
[0008] (2) subjecting the reaction liquid to a condensation reflux reaction, centrifuging, washing, and vacuum drying after the reaction is completed to obtain a precursor;
[0009] (3) grinding and sieving the precursor, adding a nitrogen source, continuing to grind evenly, and then calcining in a reducing atmosphere;
[0010] (4) The calcined product is washed in deionized water, and then filtered, dried and ground to obtain an FeMo / NC catalyst.
[0011] It is further defined that the molar ratio of the metal salt, the organic ligand and the surfactant in (1) is 1:(5-8):4.
[0012] It is further defined that the metal salt comprises a source of iron, a source of molybdenum, and a source of zinc.
[0013] It is further defined that the iron source is ferric chloride hexahydrate and / or ferric nitrate hexahydrate; the molybdenum source is ammonium molybdate and / or sodium molybdate dihydrate; and the zinc source is zinc chloride.
[0014] It is further defined that the molar ratio of the iron source to the molybdenum source is 1:1.
[0015] It is further defined that the surfactant is STAB.
[0016] Further defined, the organic ligand includes dimethylimidazole and 2-mercapto-1-methylimidazole.
[0017] It is further defined that the mass ratio of dimethylimidazole to 2-mercapto-1-methylimidazole is 9:1.
[0018] It is further defined that the oil bath temperature in (1) is 70°C and the time is 6 hours.
[0019] It is further defined that the centrifugal speed in (2) is 6050 r / min and the time is 3 min.
[0020] It is further defined that the solvent used in the washing process in (2) is ethanol or deionized water, and the number of washing times is 3 to 5 times.
[0021] It is further defined that in (3), the nitrogen source is melamine, and the mass ratio of the precursor to melamine is 50 mg:10 g.
[0022] It is further defined that the calcination process in (3) is as follows: the precursor and nitrogen source mixture are moved into a tubular furnace, nitrogen is introduced into the tubular furnace for 30 minutes to expel the air, and then a hydrogen / argon mixture is continuously introduced into the tubular furnace, and the temperature is increased to 900°C at a rate of 10°C / min, kept at this temperature for 120 minutes, and naturally cooled to room temperature.
[0023] The second object of the present invention is to provide an iron-molybdenum / NC catalyst prepared by the above method.
[0024] The third object of the present invention is to provide an application of the above-mentioned iron-molybdenum / NC catalyst, specifically for preparing the cathode of a zinc-air battery.
[0025] Beneficial effects:
[0026] The present invention adopts a constant temperature oil bath self-assembly strategy, introduces a sulfur source and a nitrogen source, and then uses a hydrogen / argon mixed calcination reduction method to generate a carbon nanotube-wrapped regular dodecahedron substrate, and forms an Fe 3 C and Mo 2 C heterojunction structure, Fe 3 C and Mo 2The synergistic effect between the catalyst and C makes the catalyst of the present invention have excellent ORR activity and long-term stability. In 0.1M KOH medium, the starting potential of ORR reaches 0.972V, the half-wave potential is 0.901V, and after 10,000 CV cycles, the potential decay is only 14mV. -2 At a current density of 1.5 volts, the charge-discharge voltage gap is 0.90 V, and the continuous cycle charge-discharge can last for 380 hours. Compared with the existing technology, it also has the following advantages:
[0027] (1) The present invention uses a compound of 2-mercapto-1-methylimidazole and dimethylimidazole as an organic ligand and introduces a sulfur source to adjust the coordination structure and promote the ORR activity of the catalyst and the growth of carbon nanotubes on the surface of the regular dodecahedron substrate.
[0028] (2) The present invention introduces a nitrogen source by adding melamine, catalyzing the formation of carbon nanotube morphology on the surface of the regular dodecahedron substrate, increasing the specific surface area and active sites, and improving the catalyst activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a scanning electron microscope photograph of the FeMo / NC catalyst prepared in Example 1;
[0030] Figure 2 a is a transmission electron microscope photo of the FeMo / NC catalyst prepared in Example 1, b is a local enlarged view of a, c is a lattice fringe spacing diagram, and d is an elemental analysis diagram;
[0031] Figure 3 LSV comparison curve of the FeMo / NC catalyst prepared in Example 1 before and after 10,000 CV cycles;
[0032] Figure 4 LSV comparison curve of commercial Pt / C catalyst before and after 10000 CV cycles;
[0033] Figure 5 The long-term operation stability curves of the FeMo / NC catalyst and the commercial Pt / C catalyst prepared in Example 1 under constant potential;
[0034] Figure 6 The FeMo / NC catalyst prepared in Example 1 and the commercial Pt / C catalyst were – 2 Charge and discharge stability curve under current density;
[0035] Figure 7 This is a scanning electron microscope photograph of the catalyst prepared in Comparative Example 1;
[0036] Figure 8This is a scanning electron microscope photograph of the catalyst prepared in Comparative Example 2;
[0037] Fig. 9 This is a scanning electron microscope photograph of the catalyst prepared in Comparative Example 3. DETAILED DESCRIPTION
[0038] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0039] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0040] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0041] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art, and the purity of the solid and liquid reagents used is analytically pure.
[0042] Example 1
[0043] The preparation method of the FeMo / NC catalyst for long-term charge and discharge cycle stability of zinc-air batteries in this embodiment is as follows:
[0044] Step 1, 15 mmol of zinc chloride, 0.25 mmol of ferric chloride hexahydrate, 0.25 mmol of ammonium molybdate, 81 mmol of dimethylimidazole and 9 mmol of 2-mercapto-1-methylimidazole were dissolved in 100 mL of DMF solution, respectively, and ultrasonically stirred for 30 min until completely dissolved, and then the solutions were mixed and stirred evenly, 4 mmol of STAB was added and stirred evenly, and then the mixture was transferred to an oil bath and heated and stirred at 70° C. for 6 h until the solution turned orange-yellow to obtain a reaction solution;
[0045] Step 2, place the reaction solution obtained in step 1 in a reaction environment with a constant temperature of 70°C to avoid the influence of temperature fluctuations on the synthesis. Before heating, the oil bath liquid level should be at 1 / 2 to 1 / 3 of the reaction container, and then condensed water should be introduced from bottom to top, and then heating should be started. Heat to 70°C for condensation reflux reaction and react for 180 minutes. When the reaction is over, the reaction bottle should be taken out of the oil bath and placed above the oil surface. After cooling, wipe the oil on the surface of the reaction bottle with paper. Then centrifuge at 6050r / min for 3 minutes, wash 3 times with deionized water as the solvent, and dry in a 70°C vacuum oven for 10 hours to obtain the precursor;
[0046] Step 3: Place 50 mg of the precursor in a ball mill and grind it evenly. Then, add 10 mg of melamine and continue grinding to obtain a mixture. Transfer the mixture to a tubular furnace, pass nitrogen for 30 minutes to exhaust the air in the tubular furnace to prevent oxygen from oxidizing the catalyst. Continue to pass hydrogen / argon mixed gas, raise the temperature to 900°C at a rate of 10°C / min, calcine for 120 minutes, and naturally cool to room temperature to obtain a catalyst.
[0047] Step 4: Dissolve 50 mg of the catalyst in 1000 mL of deionized water, stir at a speed of 500 r / min for 8 h, filter, and finally move into a 60° C. vacuum oven for drying for 8 h. Grind the mixture evenly to obtain a FeMo / NC catalyst.
[0048] The FeMo / NC catalyst obtained above was characterized, and the scanning electron microscope photos are shown in FIG. Figure 1 As shown. Figure 1 It can be seen that the microscopic morphology of the FeMo / NC catalyst is a regular dodecahedron wrapped by carbon nanotubes. Figure 2 It can be seen that Fe is loaded on the regular dodecahedron. 3 C and Mo 2 C heterojunction ( Figure 1 There are small black particles on the dodecahedron, which are Fe 3 C and Mo 2 C heterojunction).
[0049] The ORR performance of the FeMo / NC catalyst obtained above was tested, and the specific operation process was as follows:
[0050] (1) Preparation of slurry: Weigh 5 mg of FeMo / NC catalyst and grind it thoroughly. Then add 0.5 mL of 0.5% naphthol solution of binder and 1.5 mL of ethanol dispersant for ultrasonic dispersion. Take 40 μL of sample with an injection needle and drop it on the platinum carbon electrode on the rotating disk. Dry it at room temperature to obtain a platinum carbon electrode coated with slurry.
[0051] (2) Build a test device: A three-electrode system is composed of a platinum mesh as a counter electrode, a standard hydrogen electrode as a reference electrode, and a platinum carbon electrode coated with a slurry as a working electrode. Prepare an electrolyte with 0.1 M KOH, and continuously introduce high-purity oxygen into the electrolyte for 30 min until it is saturated. Perform an ORR performance test. Activate the sample by cyclic voltammetry (CV) in a voltage range of 0.2 V to 1.2 V, and obtain a polarization curve by linear stylus voltammetry (LSV). The scan rate during the LSV test is 0.01 V / s and the rotation speed is 1600 rpm.
[0052] The electrochemical performance of FeMo / NC catalyst for ORR is obtained by Figure 3 As shown in Tables 1 and 2 below, Figure 3 It can be seen that after 10,000 cycles of CV cycle test, the half-wave potential of the FeMo / NC catalyst decayed by only 14 mV.
[0053] Table 1 Comparison of half-wave and onset potentials of FeMo / NC catalyst after 10000 CV cycles
[0054] Initial 10000th <![CDATA[E 1 / 2 (VvsRHE)]]> 0.901 0.887 <![CDATA[E onset (VvsRHE)]]> 0.972 0.962
[0055] Table 2 Comparison of charge and discharge voltage gaps of FeMo / NC catalysts at different current densities
[0056] <![CDATA[J(mA·cm -2 )]]> 10 ΔE(V) 0.9
[0057] The commercial Pt / C catalyst was used to replace the FeMo / NC catalyst in Example 1. The ORR electrochemical performance of the commercial Pt / C catalyst was as follows: Figure 4 As shown in Tables 3 and 4 below, Figure 4 It can be seen that after 10,000 cycles, the half-wave potential of the Pt / C catalyst decays by 36 mV, which is higher than that of the FeMo / NC catalyst.
[0058] Table 3 Comparison of half-wave and onset potential of Pt / C catalyst before and after durability after 10000 CV cycles
[0059] Initial 10000th <![CDATA[E 1 / 2 (VvsRHE)]]> 0.885 0.864 <![CDATA[E onset (VvsRHE)]]> 1.000 0.925
[0060] Table 4 Pt / C catalyst at 10 mA cm -2 Charge and discharge voltage gap under current density
[0061] <![CDATA[J(mA·cm -2 )]]> 10 ΔE(V) 1.2
[0062] By comparing Tables 1 to 4 above, it can be seen that the FeMo / NC catalyst prepared in Example 1 has a very high half-wave potential and stability as an electrocatalyst for the ORR reaction, and also has great advantages over commercial catalysts.
[0063] The cyclic stability was further characterized and the results were as follows Figure 5 and Figure 6 As shown by Figure 5 It can be seen that after 10,000 CV cycles, the potential decays by only 14 mV, and the limiting current density can be maintained at 93.3%. Figure 6 It can be seen that the assembled liquid zinc-air battery has a current of 10 mA cm -2 The voltage difference (ΔE) is 0.9V, and after 350h of cycle stability, the voltage difference only increases by 0.02V, which has excellent cycle stability.
[0064] Comparative Example 1:
[0065] The difference between this comparative example and Example 1 is that the amount of 2-mercapto-1-methylimidazole added in step 1 is 0, and the remaining process steps and parameter settings are the same as those in Example 1.
[0066] The microstructure of the catalyst obtained in this comparative example was characterized, and the results are as follows: Figure 7 As shown by Figure 7 It can be seen that when 2-mercapto-1-methylimidazole is not added, the number of carbon nanotubes grown on the surface of the regular dodecahedron is small and the morphology and size are uneven.
[0067] Comparative Example 2:
[0068] The difference between this comparative example and Example 1 is that the amount of melamine added in step 3 is 0, and the remaining process steps and parameter settings are the same as those in Example 1.
[0069] The microstructure of the catalyst obtained in this comparative example was characterized, and the results are as follows: Figure 8 As shown by Figure 8 It can be seen that when melamine is not added, the surface of the regular dodecahedron shrinks and the number of catalytically formed tubes is small.
[0070] Comparative Example 3:
[0071] The difference between this comparative example and Example 1 is that the centrifugal speed in step 2 is 5000 r / min, and the remaining process steps and parameter settings are the same as those in Example 1.
[0072] The microstructure of the catalyst obtained in this comparative example was characterized, and the results are as follows: Fig. 9 As shown by Fig. 9 It can be seen that the FeMo / NC catalyst synthesized after centrifugation at a low speed is prone to aggregation, which is not conducive to the subsequent calcination to form a dispersed morphology with uniform size.
[0073] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing an iron-molybdenum / NC catalyst, characterized in that: include: (1) dissolving the metal salt, the organic ligand and the surfactant in DMF respectively, stirring them by ultrasonic until they are completely dissolved and then mixing them evenly, placing them in an oil bath and stirring at a constant temperature to obtain a reaction solution; (2) subjecting the reaction liquid to a condensation reflux reaction, centrifuging, washing, and vacuum drying after the reaction is completed to obtain a precursor; (3) grinding and sieving the precursor, adding a nitrogen source, continuing to grind evenly, and then calcining in a reducing atmosphere; (4) The calcined product is washed in deionized water, and then filtered, dried and ground to obtain an FeMo / NC catalyst.
2. The preparation method according to claim 1, characterized in that: (1) The molar ratio of the metal salt, the organic ligand and the surfactant is 1:(5-8):4; the metal salt includes an iron source, a molybdenum source and a zinc source, the surfactant is STAB, and the organic ligand includes dimethylimidazole and 2-mercapto-1-methylimidazole.
3. The preparation method according to claim 2, characterized in that: The mass ratio of dimethylimidazole to 2-mercapto-1-methylimidazole is 9:
1.
4. The preparation method according to claim 2, characterized in that: The iron source is ferric chloride hexahydrate and / or ferric nitrate hexahydrate; the molybdenum source is ammonium molybdate and / or sodium molybdate dihydrate; the zinc source is zinc chloride; and the molar ratio of the iron source to the molybdenum source is 1:
1.
5. The preparation method according to claim 1, characterized in that: (1) The oil bath temperature is 70°C and the time is 6 hours.
6. The preparation method according to claim 1, characterized in that: (2) The centrifugal speed is 6050 r / min and the time is 3 min.
7. The preparation method according to claim 1, characterized in that: (3) The nitrogen source is melamine, and the mass ratio of the precursor to melamine is 50 mg:10 g.
8. The preparation method according to claim 1, characterized in that: (3) The calcination process is as follows: the precursor and nitrogen source mixture are moved into a tubular furnace, nitrogen is introduced into the tubular furnace for 30 minutes to exhaust the air, and then a hydrogen / argon mixture is continuously introduced, and the temperature is increased to 900°C at a rate of 10°C / min, kept at this temperature for 120 minutes, and naturally cooled to room temperature.
9. An iron-molybdenum / NC catalyst prepared by the method according to any one of claims 1 to 8.
10. Use of the iron-molybdenum / NC catalyst according to claim 9, characterized in that: Used to prepare the cathode of zinc-air batteries.
Citation Information
Patent Citations
Preparation method of zinc-air battery catalyst and application thereof in catalyzing ORR, OER and HER reactions
CN109037710A
Preparation of non-noble metal / carbon composites based on metal-organic framework, non-noble metal / carbon composites and their applications
CN109216712A
Molybdenum-based nitride / carbide electrocatalyst and preparation method and application thereof
CN114214657A
FeNi-N-C composite electrochemical catalyst based on MOFs structure
CN116344848A
Nitrogen-doped carbon nanofiber supported iron monatomic / molybdenum carbide catalyst as well as preparation method and application thereof
CN117512654A